Seasonal Dynamics of Microbial Communities in PM2.5 and PM10 from a Pig Barn - Qian Tang; Minyang Zhang; Lili Yu; Kaidong Deng; Huihua Mao; Jingwen Hu; Chuang Wang (Animals)
Modern, intensive, high-density farming practices cause elevated concentrations of particulate matter (PM) inside livestock barns. PM in livestock barns is predominantly biological, hence, it contains abundant microorganisms. Understanding the microbial composition of PM is crucial for assessing the hazards of air emitted from livestock barns. PM10 and PM2.5 from a pig barn were collected in winter and spring, and morphological, chemical, and microbial analyses were performed. The PM samples exhibit diverse morphological characteristics. The top three elements detected in the PM samples were O, C, and Si. Other elements, including N, Al, K, Mg, Ca, Na, Zn, P, W, Ba, Fe, S, Cl, and Ti, were also identified in these samples. For bacterial α diversity, the Sobs and Chao1 indices for PM10 were significantly higher than those for PM2.5 in winter (p < 0.05), and in spring, the ACE index for PM10 was significantly higher than that for PM2.5 (p < 0.05). For fungal α diversity, the Shannon index for PM10 was significantly higher than that for PM2.5 in winter (p < 0.01), and in spring, the Ace index for PM10 was significantly higher than that for PM2.5 (p < 0.05). The β diversity results indicate that season, rather than the particle size, had a significant effect on the microbial composition in the PM samples. A total of seven bacterial pathogen genera and 16 fungal allergen genera were identified in PM samples. In winter, the relative abundances of total bacterial pathogens and fungal allergens in PM2.5 were higher than those in PM10. In contrast, the relative abundance of fungal allergens in PM10 was higher in spring than in winter. This study provides a comprehensive characterization of PM from a pig barn across the particle sizes and seasons.